Ukrainian military-economic nuclear bomb has already exploded in Russia's economy (retrospective, present and future) - Semenenko, Oleh; Dobrovolskyi , Yuzef; Yarmolchyk , Maria; Rakhmanyi , Oleksandr; Tarasov , Oleh; Remez , Artem (Social Development and Security, 2022)
Purpose: to reveal a retrospective of Russia's preparations for war with Ukraine, to determine the main military and economic features and consequences of the Russian-Ukrainian war on Russia's economy, to form possible projected options for the state of Russia's economy from the development of scenarios and duration of hostilities between Russia and Ukraine.Design/Method/Approach: the main research methods are methods of statistical analysis, military-economic analysis, expert survey and forecasting methods. Findings: analyzed the dynamics of the Russian economy before the Russian-Ukrainian war, determined the impact of sanctions against Russia on its economy today and predicted the state of recession in Russia's economy with different options for the development of hostilities and their duration, as well as possible military and economic risks for Russia in the future. Theoretical implications: The main result of research on the subject of the article is the formation of a baseline database on the effects of the Ukrainian military-economic bomb on Russia's economy, taking into account the analytical retrospective results of Russia's participation in previous wars and armed conflicts.Paper type: descriptive and calculation-analytical.